Verboten und verbrannt : deutsche Literatur 12 Jahre unterdrückt - Drews, Richard 1902-1972 Hrsg; Kantorowicz, Alfred 1899-1979; Kindler, Helmut 1912-2008; Jens, Walter 1923-2013 (Kindler, 1983)
Neuauflage